Canopy‐Mediated Dynamics of Moss Communities in Primary Succession: Coupling of N2‐Fixation and Biomass Accumulation in Subalpine Forests Following Glacial Retreat - Jie Deng; Genxu Wang; Shouqin Sun; Wentian Xie; Feng Long; Zhaoyong Hu; Juying Sun; Xiangyang Sun; Thomas H. DeLuca (Ecology and Evolution, 2025)
ABSTRACT Accelerated glacial retreat has exposed bare substrates in polar and alpine regions, creating opportunities for investigating primary vegetation succession. Mosses are pioneer species critical for soil development, nutrient cycling, and establishment of subsequent vegetation succession. However, the dynamics of moss communities during primary succession and their responses to canopy‐mediated environmental changes are poorly known. We investigated moss bottom community dynamics along a 129‐year primary successional gradient from barren land to coniferous climax forest on a deglacial foreland in eastern Qinghai‐Tibet Plateau. Additionally, we conducted a reciprocal transplant experiment and a canopy tree litter addition experiment at three succession stages with distinct canopy densities to explore the effects of shifts in canopy composition on the development of the moss bottom layer. Moss biomass and cover in the bottom layer had a nonlinear and fluctuating growth pattern across the primary successional chronosequence, in which successional stages with higher canopy density had lower moss cover and biomass. Transplantation of moss carpets from open to denser canopy stages or canopy litter additions enhanced photosynthetic rates, but suppressed N2‐fixation rates and moss growth. Variations in N2‐fixation and photosynthesis rates were related to daylight hours, relative humidity, and throughfall N levels. Changes in moss bottom layer cover and biomass over the successional chronosequence were positively related to N2‐fixation and regulated by canopy leaf litter and throughfall N inputs. Our results demonstrate a strong coupling between moss biomass and cyanobacterial N2‐fixation, alongside a decoupling of moss photosynthesis from productivity during primary succession following glacial retreat. The effects of canopy cover and composition on moss productivity, photosynthesis, and N2‐fixation rates represent a dynamic set of canopy‐bottom layer interactions that may shape the structure and function of developing subalpine forest.